Electro acoustic analogies in MatLab environment - Kulička, Jiří (Univerzita Pardubice, 2010)
Analogy is a cognitive process of transferring information from a specific object (source) to another specific object (goal), in this case means a mathematical similarity between different physical systems and processes. This article deals with the method of calculating the resonant frequency acoustic system on the basis of electro acoustic analogy, based on isomorphism various physical systems - electrical, mechanical, hydraulic and electro acoustic. Acoustic systems can be created by combining their individual components, like electrical circuits or mechanical and hydraulic systems. The acoustic resonance in the system always takes place when it has alternating power and its impact coincides with the natural frequency of vibration. The article created electro acoustic model of flute, which is studied using a computer model in an environment of Matlab and Simulink. The model works by calculating the acoustic impedance, which is determined by the resonant frequencies. Resonance occurs always in zero point graph of a function, the impedance changes its value from negative to positive. This model leads to very decent results when we compared the theoretical values of resonant frequencies with calculated. The possibility of experimental investigation of acoustic systems, the equivalent electrical circuit is in economic terms, time and according to the results and accuracy of better solutions than the investigation of their own systems. The model can be used to design dimensions of the flutes and other acoustic systems, or to improve their debugging.
Keywords: auditory system; resonant frequency; electro acoustic analogy; electro acoustic model; flute; Matlab; acoustic impedance